Draft Annual Plan 1990-91 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1990)
Arunachal Pradesh is situated in the North- Eastern part of India. It borders the plans of Brahmaputra and gradually rises up in hills towards Himalayas and reaches over to 7,300 mtrs at Gorichen in West Kameng Distt. It has international, border with Bhutan in the West, China in North and North-East and Burma in the East. The total length of international border is about 1,628 KM. It has inter-state borders with Nagaland in South-East and East & East and with Assam in the South.
Government of Arunachal Pradesh, Planning and Development Department